2012
DOI: 10.1002/dev.21089
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol pre‐exposure during adolescence or adulthood increases ethanol intake but ethanol‐induced conditioned place preference is enhanced only when pre‐exposure occurs in adolescence

Abstract: Behavioral sensitization has been suggested to contribute to uncontrolled alcohol consumption. The aim of this study was to investigate the effects of repeated ethanol administration in adolescent and adult mice on subsequent ethanol consumption and conditioned place preference (CPP). Mice were administered ethanol for 15 consecutive days. This ethanol regimen induced behavioral sensitization to a lesser degree in adolescents than in adults. Following ethanol treatment, mice were subjected to CPP procedure, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 91 publications
4
25
0
Order By: Relevance
“…The present study also highlights that neural adaptations in response to repeated ethanol and stressors differ between adolescents and adults. We have demonstrated that adolescents are less sensitive to ethanol-induced sensitization than adults (Carrara-Nascimento, Griffin, Pastrello, Olive, & Camarini, 2011;Carrara-Nascimento, Olive, & Camarini, 2014;Faria et al, 2008), and here we extend this lower sensitivity also to CUS-ETOH cross-sensitization. Locomotor sensitization and crosssensitization are behavioral proxies of alcohol/stress-induced neuroadaptations, and the complexity of the brain development during adolescence may explain age differences in those behavioral responses to ethanol/stress.…”
Section: Discussionsupporting
confidence: 76%
“…The present study also highlights that neural adaptations in response to repeated ethanol and stressors differ between adolescents and adults. We have demonstrated that adolescents are less sensitive to ethanol-induced sensitization than adults (Carrara-Nascimento, Griffin, Pastrello, Olive, & Camarini, 2011;Carrara-Nascimento, Olive, & Camarini, 2014;Faria et al, 2008), and here we extend this lower sensitivity also to CUS-ETOH cross-sensitization. Locomotor sensitization and crosssensitization are behavioral proxies of alcohol/stress-induced neuroadaptations, and the complexity of the brain development during adolescence may explain age differences in those behavioral responses to ethanol/stress.…”
Section: Discussionsupporting
confidence: 76%
“…This developmental effect, that drinking during adolescence leads to a different profile of behavior than drinking during adulthood, has also been shown in mice. Carrara-Nascimento, Olive & Camarini (2014) found that adolescent and adult alcohol-exposed mice consumed the same amount of alcohol after a 15-day treatment (2 g/kg injection) but only the adolescent-exposed mice showed a robust preference during the condition-place preference paradigm. These results indicate that administration of ethanol during adolescence can alter future behaviors in a different manor than when administered in adulthood.…”
Section: Discussionmentioning
confidence: 94%
“…None the less, future studies are needed to further investigating the appetitive and motivational impact of adult alcohol exposure. Previous studies have shown that pre-exposure to ethanol in adulthood increased future consumption (de la Torre, Escarabajal & Agüero, 2015; Carrara-Nascimento, Olive & Camarini, 2014). While pre-exposure increased consumption in both adolescent and young adult rats, it modestly increased the motivation to consume alcohol in the adolescent-exposed rats compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol exposure during adolescence can cause dramatic neurobehavioral and neurotoxicological effects compared to exposure during adulthood, as described in humans (Grant and Dawson, 1997; De Wit et al, 2000; Ehlers et al, 2006) and rodents (Crews et al, 2000; Faria et al, 2008; Walker and Ehlers, 2009; Guerri and Pascual, 2010; Soares-Simi et al, 2013; Carrara-Nascimento et al, 2014). …”
Section: Introductionmentioning
confidence: 97%
“…Drinking in the dark (DID) paradigm is considered a binge-like model since it promotes high levels of blood ethanol concentration (Rhodes et al, 2005). Another procedure to promote increase in ethanol consumption is to preexpose the animals to the drug (Lessov et al, 2001; Camarini and Hodge, 2004; Carrara-Nascimento et al, 2014). …”
Section: Introductionmentioning
confidence: 99%